Peranan Hukum Adat Sasi Laut dalam melindungi Kelestarian Lingkungan di desa Eti Kecamatan Seram Barat Kabupaten Seram Bagian Barat (Lex Jurnalica, 2008)
Environment preservation efforts for moluccas society that proved wrongly one moluccas society culture that known by the name of “ sasi “. Sasi prohibition to harvest certain resource (also land sea biological) within that appointed with a purpose to as efforts to protect tradition, increase village income and protect sumberdaya from also society at village self. The important part sasi in preserve batural resources here's, so that be formed a customary law regulation sasi that must be obeyed during sasi be carried out and when found infringements that done be worn sanction as according to rule that appointed. Troubleshoot is lifted in this study that is: how efektifity customary law sasi sea towards positive law in Indonesia, especially related to environment troubleshoot and what done towards custom transgression sasi. writing this study based in law watchfulness method normatif empirical where done with interview and observation. As according to watchfulness that done at village eti eery district west part eery regency west, so inferential that customary law sasi very effective because society can not dare to take resource nature prior to open sasi. Law action that done towards custom transgression sasi that is when is there that break regulation hitted sanction as according to infringement that maked it good that sanction from village government, sanction from ancestors with sanction from god. Sanction stipulating at village eti made by village government and saniri country that has aim to support regulation that appointed at village. Moluccas society must can preserve and obey all customary law regulations sasi because with customary law existence sasi batural resources can awake well.Keywords: Customary Law, Sasi Sea, Environment